2004
DOI: 10.1038/sj.ejcn.1601872
|View full text |Cite
|
Sign up to set email alerts
|

Number of days needed to assess energy and nutrient intake in infants and young children between 6 months and 2 years of age

Abstract: Objective: To estimate the minimum number of days of recorded dietary intake needed to place infants and young children into thirds of a population distribution with an acceptable degree of accuracy. Design: Dietary intake data collected from 5-day weighed food records for 72 infants and young children up to 2 y of age, collected during a cross-sectional study, were analysed to estimate the number of recording days necessary to assess intake of energy and 10 nutrients. Setting: Community study among healthy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
60
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 7 publications
8
60
0
1
Order By: Relevance
“…The interpersonal variance found by the present study was the greatest source of nutrient intake variance, resulting in a VR of less than 1 and corroborating the findings of Laningan et al 1 in children and Herbert et al 24 in adults. The lack of variation in habitual dietary intake can be attributed to the low purchasing power and low education levels of the study population.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The interpersonal variance found by the present study was the greatest source of nutrient intake variance, resulting in a VR of less than 1 and corroborating the findings of Laningan et al 1 in children and Herbert et al 24 in adults. The lack of variation in habitual dietary intake can be attributed to the low purchasing power and low education levels of the study population.…”
Section: Discussionsupporting
confidence: 80%
“…Assessing habitual food intake is complex because it involves factors related to daily intake variability, information reliability and identification of under-or overreporting [1][2][3] . Food intake and variance estimates differ among populations, genders, age groups and cultures 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies of estimated food records in children and adolescents have shown an underestimation of food intake by up to 35% (Bandini et al, 1997;Champagne et al, 1998;Singh et al, 2009). However, only little research on the validation of dietary intake methodology in infants and young children exists (Davies et al, 1994;Lanigan et al, 2004;Burrows et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Although different studies have characterized within-and between-person variance for energy and nutrient intakes in adults 10,11 very little information is available for children 12,13 , especially in Brazil. In addition, most studies of the child population are usually held in public health institutions and at nursery schools 14,15,16,17,18 and few population-based studies have been conducted in recent years 19,20,21,22 .…”
Section: Introductionmentioning
confidence: 99%